Decompressive craniectomy for severe traumatic brain injury patients with fixed dilated pupils - Mao X; Miao G; Hao S; Tao X; Hou Z; Li H; Tian R; Zhang H; Lu T; Ma J; Zhang X; Cheng H; et al. (Dove Medical Press, 2015)
Xiang Mao,1,3–5,* Guozhuan Miao,6,* Shuyu Hao,2–5,* Xiaogang Tao,2–5 Zonggang Hou,2–5 Huan Li,2–5 Runfa Tian,2–5 Hao Zhang,1–6 Te Lu,2–5 Jun Ma,7 Xiaodong Zhang,1 Hongwei Cheng,1 Baiyun Liu2–6 1Department of Neurosurgery, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 2Department of Neurosurgery, Beijing Tian Tan Hospital, Capital Medical University, 3Nerve Injury and Repair Center of Beijing Institute for Brain Disorders, 4Neurotrauma Laboratory, Beijing Neurosurgical Institute, Capital Medical University, 5China National Clinical Research Center for Neurological Diseases, 6Department of Neurotrauma, General Hospital of Armed Police Forces, 7Imaging Center of Neuroscience, Beijing Tian Tan Hospital, Capital Medical University, Beijing, People’s Republic of China *These authors contributed equally to this work Objective: The outcome of decompressive craniectomy (DC) for severe traumatic brain injury (sTBI) patients with fixed dilated pupils (FDPs) is not clear. The objective of this study was to validate the outcome of DC in sTBI patients with FDPs. Patients: We retrospectively collected data from 207 sTBI patients with FDPs during the time period of May 4, 2003–October 22, 2013: DC group (n=166) and conservative care (CC) group (n=41). Measurements: Outcomes that were used as indicators in this study were mortality and favorable outcome. The analysis was based on the Glasgow Outcome Scale recorded at 6 months after trauma. Results: A total of 49.28% patients died (39.76% [DC group] vs 87.80% [CC group]). The mean increased intracranial pressure values after admission before operation were 36.20±7.55 mmHg in the DC group and 35.59±8.18 mmHg in the CC group. After performing DC, the mean ICP value was 14.38±2.60 mmHg. Approximately, 34.34% sTBI patients with FDPs in the DC group gained favorable scores and none of the patients in the CC group gained favorable scores. Conclusion: We found that DC plays a therapeutic role in sTBI patients with FDPs, and it is particularly important to reduce intracranial pressure as soon as possible after trauma. For the patients undergoing DC, favorable outcome and low mortality could be achieved. Keywords: decompressive craniectomy, severe traumatic brain injury, fixed dilated pupils, intracranial pressure